2015
DOI: 10.3390/metabo5040733
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Plant Metabolites in the Management of Non-Communicable Metabolic Diseases: Looking at Opportunities beyond the Horizon

Abstract: There has been an unprecedented worldwide rise in non-communicable metabolic diseases (NCDs), particularly cardiovascular diseases (CVD) and diabetes. While modern pharmacotherapy has decreased the mortality in the existing population, it has failed to stem the rise. Furthermore, a large segment of the world population cannot afford expensive pharmacotherapy. Therefore, there is an urgent need for inexpensive preventive measures to control the rise in CVD and diabetes and associated co-morbidities. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 190 publications
(238 reference statements)
0
12
0
Order By: Relevance
“…High fat diets have demonstrated the ability to be a good model of obesity and metabolic syndrome in laboratory animals models [6][7][8]56,58,59]. However, the efficiency in the use of energy also influences the development of obesity in rodents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High fat diets have demonstrated the ability to be a good model of obesity and metabolic syndrome in laboratory animals models [6][7][8]56,58,59]. However, the efficiency in the use of energy also influences the development of obesity in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the effects of thyroid status on hepatic pGluAP and the release of endogenous peptides as cyclo His-Pro (cHP) are determinant in insulin sensitivity and body weight control [56,57]. In our results, HFDs significantly increased the soluble pGluAP activity in the liver (Figure 2A: S, 1.0 ± 0.1 pmol (×10 2 )/min/mg protein; VOO, 1.5 ± 0.0 pmol (×10 2 )/min/mg protein; Bch, 1.4 ± 0.0 pmol (×10 2 )/min/mg protein).…”
Section: Hepatic Trh-degrading Pyroglutamate Aminopeptidase Activity mentioning
confidence: 99%
“…Human health is determined by various interacting factors, among which lifestyle, environment, and diet play an important synergistic role in the prevention of several diseases, including cancers. Human intervention trials have provided evidence for protective effects of various polyphenol‐rich foods against chronic disease, including cardiovascular disease, neurodegeneration, and cancer . While there are considerable data suggesting the benefits of polyphenol rich‐diet, conclusions regarding their preventive potential remain unresolved due to several limitations in existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of functional foods include foods that contain specific minerals, vitamins, fatty acids or dietary fibers, foods with added biologically active substances, such as phytochemicals or other antioxidants and probiotics that contain live beneficial bacterial cultures. 12,13 The sweetness of xylose is about 70% of cane sugars. D-Xylose is accepted by the US Food and Drug Administration as a safe food ingredient (GRAS).…”
Section: Discussionmentioning
confidence: 99%